2009
DOI: 10.1144/sp316.3
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoseismology of the North Anatolian Fault near the Marmara Sea: implications for fault segmentation and seismic hazard

Abstract: We conducted palaeoseismic studies along the North Anatolian fault both east and west of the Marmara Sea to evaluate its recent surface rupture history in relation to the well-documented historical record of earthquakes in the region, and to assess the hazard of this major fault to the city of Istanbul, one of the largest cities in the Middle East. Across the 1912 rupture of the Ganos strand of the North Anatolian fault west of the Marmara Sea, we excavated 26 trenches to resolve slip and constrain the earthqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 25 publications
5
53
0
2
Order By: Relevance
“…Rockwell et al [2009]did not use an OxCal model for this site, we ran a model using all of the dates and found a very poor fit, which we attributed to the reworking of sample 6. By excluding this sample our model is consistent with the appropriately vague interpretation of historical earthquakes described by Rockwell et al [2009].…”
Section: Appendix B: Review Of Published Paleoseismic Investigationsmentioning
confidence: 92%
See 3 more Smart Citations
“…Rockwell et al [2009]did not use an OxCal model for this site, we ran a model using all of the dates and found a very poor fit, which we attributed to the reworking of sample 6. By excluding this sample our model is consistent with the appropriately vague interpretation of historical earthquakes described by Rockwell et al [2009].…”
Section: Appendix B: Review Of Published Paleoseismic Investigationsmentioning
confidence: 92%
“…These data were used along with additional data by Rockwell et al [2009] to constrain the timing of two paleoearthquakes and clear evidence of the 1999 İzmit earthquake. Using the fraction modern carbon presented by Rockwell et al [2009], we determine the unrounded conventional radiocarbon ages that are included in the paleoearthquake model.…”
Section: Appendix B: Review Of Published Paleoseismic Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…When we considered these earthquakes' locations, formation timings and magnitudes, it seems that the large earthquakes, which eventuated on the EFZ and were quite close to the YGFZ, triggered each other. The palaeoseismological studies carried out in the northern branch of the NAFZ suggested that the estimated recurrence interval is 150-300 years for surfaceruptured large earthquakes (Hartleb, Dolan, Kozaci, Akyuz, & Seitz, 2006;Ikeda et al, 1991;Kozacı, Dolan, & Finkel, 2009;Kozacı, Dolan, Yönlü, & Hartleb, 2011;Özaksoy et al, 2010;Rockwell, Barka, Dawson, Akyuz, & Thorup, 2001;Rockwell et al, 2009), while palaeoseismological studies on the southern branch are very limited, except for Yoshioka and Kuşçu (1994), Kürçer et al (2008), Belindir (2008) and Özalp et al (2013); however, Özalp et al (2013) reported that the return period of the greater earthquakes that occurred on the southern branch was not regular, but these fault segments have the potential to produce earthquakes on the northern branch. Additionally, Belindir (2008) reported an earthquake recurrence interval on the YGFZ that ranged between 253 and 925 years.…”
Section: Interpretation Of Palaeoseismological and Geoarchaeological mentioning
confidence: 99%